Study of Existing Conditions as Preservation Rumah Lontiok of Kendil Kemilau Emas Foundation - Muhd. Arief Al Husaini; Wahyu Hidayat; Mashuri; Sri Djuniati; Ahmad Nawawi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Lontiok House is one of the cultural heritage of the community that has architectural appeal because it has cultural acculturation of mainland Malay people with a thick blend of Islamic culture. This study examines the existing condition of the damaged Lontiok house. This damage collection is the initial stage of efforts to preserve Rumah Lontiok. Several factors cause damage to the Lontiok House, namely the age of the old building, the influence of weather, mold, and being eaten by insects. This study conducted field observations and interviews with building managers, namely the Golden Shine Kendil Foundation. From this research, it can be obtained that all building elements are damaged so repair efforts are needed, both treating partially damaged and replacing building elements.